Comparing the risk of hepatitis B virus reactivation between direct‐acting antiviral therapies and interferon‐based therapies for hepatitis C. Issue 12 (29th July 2017) - Kawagishi, N.; Suda, G.; Onozawa, M.; Kimura, M.; Maehara, O.; Ohara, M.; Izumi, T.; Umemura, M.; Ito, J.; Nakai, M.; Sho, T.; Natsuizaka, M.; et al.
Summary: Hepatitis B virus (HBV) reactivation has been reported during antihepatitis C treatment in patients with hepatitis C virus (HCV) and HBV co‐infection. We aimed to evaluate the frequency and risk factors of HBV reactivation during anti‐HCV therapy and compared those between interferon (IFN)‐free direct‐acting antiviral (DAA) therapies and IFN‐based therapies. Three hundred and twenty‐two patients with HCV infection receiving anti‐HCV therapy were retrospectively screened. The baseline HBV infection statuses of all eligible patients and the HBV‐DNA level of all patients with current or previous HBV infection were examined at the end of treatment. In patients with baseline anti‐HBs positivity, changes in anti‐HBs titre were evaluated. Of 287 patients who met the inclusion criteria, 157 had current (n=4) or previous (n=153) HBV infection; 85 were treated with IFN‐free DAA therapies and 72 were treated with IFN‐based therapies. Six patients experienced HBV reactivation (n=2) or HBV reappearance (n=4) after IFN‐free DAA therapies, while no patient developed HBV reactivation after IFN‐based therapies. The risk factors of HBV reactivation or reappearance were DAA therapies and a reduction in anti‐HBs titre to <12 mIU mL −1 by the end of treatment. The decline changes of anti‐HBs titre were significantly higher in patients treated with DAA therapies. Although HBV reactivation hepatitis was not observed, three of four patients with HBV reactivation or reappearance after achieving HCV eradication had viremia 8 weeks after completion of therapy. A significant proportion of patients develop HBV reactivation or reappearance without hepatitis after IFN‐free DAA therapies. Low levels of anti‐HBs and their decrease to <12 mIU mL −1 after treatment are significant risk factors for HBV reactivation or reappearance.